1999
DOI: 10.1038/sj.bmt.1702009
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide and paclitaxel as initial or salvage regimen for the mobilization of peripheral blood progenitor cells

Abstract: Summary:Peripheral blood progenitor cells are now commonly used for hematologic reconstitution after myelosuppressive chemotherapy for hematologic and solid malignancies. The purpose of this study was to evaluate the activity of paclitaxel 170 mg/m 2 and cyclophosphamide 2 g/m 2 (CP) with filgrastim (human G-CSF) for mobilization of PBPCs as the first or second maneuver after failure with filgrastim alone. Sixty-four patients with stage II-IV breast cancer received (CP) followed by filgrastim (10 g/kg/day). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…injection of 250 mg/kg body weight of cyclophosphamide (CPA) or Phosphate Buffered Saline (PBS, control). This dose is similar to that used in humans receiving high dose CPA (14). …”
Section: Methodsmentioning
confidence: 99%
“…injection of 250 mg/kg body weight of cyclophosphamide (CPA) or Phosphate Buffered Saline (PBS, control). This dose is similar to that used in humans receiving high dose CPA (14). …”
Section: Methodsmentioning
confidence: 99%
“…The most reliable time for harvesting hematopoietic stem cells is still under investigation, but after a chemotherapy‐induced nadir, collections usually are begun when the white blood cells (WBC) count recovers to >1–3 × 10 9 /L (5,6,20,21). Recently, some reported that successful mobilization critically depends on accurate monitoring of the preleukapheresis circulating CD34+ cells/μL and their timely collection (12,22–26). Therefore, we investigated the correlation of the numbers of preleukapheresis circulating CD34+ cells/μL, WBC, and platelet counts with the numbers of collected CD34+ cells.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The other available taxane, paclitaxel, has been shown to be an effective PBPC mobilizer as a single agent and in combination with cyclophosphamide and etoposide, epirubicin, ifosfamide and high-dose cyclophosphamide. [8][9][10][11][12][13][14][15] As single agents, both docetaxel and paclitaxel induce WBC nadirs of brief duration without severe thrombocytopenia. Docetaxel can be safely administered on an outpatient basis as it causes minimal nausea and vomiting and does not require aggressive intravenous hydration as do the more traditional chemotherapeutic mobilizing regimens involving high-dose cyclophosphamide.…”
mentioning
confidence: 99%